'I want to know where my child is at all times' – field study of a location-aware safety service for schoolchildren. Issue 10 (2nd October 2016) - Ervasti, Mari; Laitakari, Juhani; Hillukkala, Mika
ABSTRACT: This paper reports the findings of a long-term field study of the location-aware safety service for schoolchildren comprising a unique set-up of four service components from different service providers. End-users were closely involved as active and equally valued contributors in the participatory co-design study. The objective was to create a solution that would be suitable for common use by all end-user groups. As a result, a wearable safety gadget service was developed to answer the need to secure the independent mobility of primary schoolchildren via continuous and real-time monitoring of children's movements when out of the home. User experiences were investigated through a variety of complementary data collection methods. Children were the most pleased user group, even though the service seemed to serve primarily their parents and teachers, the most distinctive value arising from the feeling of reassurance. Study findings direct future development efforts towards a personal alerting system that would become more integrated into everyday life. Our research provides valuable insights regarding the monitoring of a child on a situational basis, helping to derive design implications for developing a children's safety solution that truly aligns with the values, needs, and practices of all stakeholders.